Distributional Effects of Imputed Rents in Five European Countries - Joachim R. Frick; Markus M. Grabka; Timothy M. Smeeding; Panos Tsakloglou (Journal of Housing Economics, 2010)
Most empirical distributional studies of well-being in developed countries rely on distributions of disposable income. From a theoretical point of view this practice is contentious since a household's command over resources is determined not only by its spending power over commodities it can buy in the market but also on resources available to the household members through non-market mechanisms such as the in-kind provisions of the welfare state and the value of private non-cash incomes. In developed market economies the most important private non-cash income component is imputed rent from owner-occupied or subsidized accommodation. Employing a wider definition of imputed rent that also allows the analyst to capture income advantages among tenants living in rent-subsidized accommodations of various sorts (including rent-free or reduced-rent households), the present paper examines the differential effects of including imputed rents in the concept of resources in five European countries (Belgium, Germany, Greece, Italy and the UK). The results suggest that in almost all cases, the inclusion of imputed rents in the concept of resources leads to a decline in measured levels of inequality and poverty. The main beneficiaries are outright homeowners and households living in rent-free (or heavily subsidized) accommodation—most often older persons. The inclusion of imputed rents in the concept of resources does not lead to substantial changes in the ranking of the countries according to their level of inequality, despite widespread differences in the rates of home ownership and subsidization across the countries studied here.
Additional information: This is the author's version of a work that was accepted for publication in the Journal of Housing Economics. Changes resulting from the publishing process, such as peer review, editing, corrections, structural formatting, and other quality control mechanisms may not be reflected in the document. Changes may have been made to this work since it was submitted for publication. A definitive version was subsequently published in Journal of Housing Economics 19 (2010), 3, pp. 167-179 and is online available at http://dx.doi.org/10.1016/j.jhe.2010.06.002.
Keywords: 330; Home ownership; Income in-kind; Imputed rent; Income distribution; Bauwirtschaft; Wohneigentum; Einkommensumverteilung; Belgien; Deutschland; Griechenland; Italien; Großbritannien